Deceleration: Revealed Preference in Society and Win-Win-Strategy for Sustainable Management - Edeltraud Günther; Marco Lehmann-Waffenschmidt (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2007)
Until recently "deceleration" has been little recognized as a technical term or as an idea, but now it seems to be getting more attention. Despite time is a decisive factor for the productivity and competitive advantages of companies continual acceleration may well be counter-productive and lead to an "acceleration paradox" – more of it not always is better. Three levels of the emergence and spread of the acceleration phenomenon can be distinguished: the macroeconomic, the microeconomic, and the motivational and behavioural level, all of them bearing, however, the danger of an "acceleration trap". Despite possible damages of acceleration deceleration processes usually seem only to be accepted if they are win-win strategies, i.e., if they have a positive impact on ecological and human targets and foster company interests at the same time. The study provides three case studies where win-win situations are realized. Going one step further, however, one can also find a preference for deceleration of agents if deceleration and economic goals are conflicting. How can the agents' willingness to pay for deceleration in such trade-off situations be measured? We do a first step in his direction with three experiments which were conducted at the Technical University of Dresden. In the first experimental setting the subjects are confronted with a trade-off between gaining a possibly higher financial reward by solving mental exercises more quickly and decelerating by taking refreshment brakes during the exercises at the expense of a potentially lower reward. In the second and the third settings subjects are virtually offered an accelerated and a decelerated alternative (more stress for higher income; more stress for faster technical progress of personal computers). The empirical evidence of all three experiments are fully consistent with the expectation that deceleration has a positive value to the subjects.
Keywords: D12; C99; D01; C91; D24; 330; Acceleration; deceleration; acceleration trap; win-win strategy; individual willingness to pay; Zeit; Betriebliche Terminplanung; Nachhaltige Entwicklung; Willingness to pay; Experiment; Theorie